Necrotizing enterocolitis comes in different forms: Historical perspectives and defining the disease. Issue 6 (December 2018) - Neu, J.; Modi, N.; Caplan, M.
Abstract: The specific cause of what is commonly referred to as necrotizing enterocolitis (NEC) disease has been elusive largely because it is becoming clear that this entity represents more than one disease with multifactorial pathogenic mechanisms. Furthermore, finding clear and consistent diagnostic biomarkers will be difficult until the different subsets of what we are calling this disease are better delineated. In this introductory chapter, we discuss different disease entities that are frequently termed "NEC" in the newborn infant. We hope this will set the stage for more focused research and development of preventative measures for at least the most common forms of this disease.